Determinan of Exchange Market Pressure in ASEAN Inflation Targeting Countries - Lisa Gusmanita; Nury Effendi; Rudi Kurniawan (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: The global economic turmoil on domestic economy was seen in 1997/1998 crisis which led to Thailand, Philippines and Indonesia implementing Inflation Targeting (IT). Empirically, IT was able to reduce foreign exchange market pressure but crisis occurred again in 2008 and large foreign exchange market pressure in 2018. This study uses Exchange Market Pressure (EMP) to examines foreign exchange market pressure in ASEAN IT countries. According to Panday (2015), EMP is percentage change in exchange rate, foreign exchange reserve, interest rate or combinations. This study aims to find determinant of EMP which can be used by monetary authority controlling pressure on foreign exchange market. Panel data analysis during 2010.Q1-2018.Q4 shows that domestic credit has significant negatively effect to EMP which indicates that domestic credit growth is in line with increasing net capital flows. Current account and US inflation have significant negatively effect while real GDP does not have significant.Keywords: Exchange Market Pressure, EMP, Exchange Rate, Monetary PolicyDeterminan Exchange Market Pressure Negara Inflation Targeting di ASEANAbstrak: Gejolak perekonomian global terhadap perekonomian domestik terlihat pada krisis 1997/1998 yang menyebabkan Thailand, Filipina dan Indonesia menerapkan Inflation Targeting (IT). Secara empiris, IT mampu menurunkan tekanan pasar valas akan tetapi krisis kembali terjadi di 2008 dan tekanan pasar valas yang besar di 2018. Penelitian ini menggunakan Exchange Market Pressure (EMP) untuk melihat seberapa besar tekanan terhadap pasar valas negara IT di ASEAN. Menurut Panday (2015), EMP adalah persentase perubahan nilai tukar, perubahan cadangan devisa, perubahan suku bunga dan atau kombinasinya. Penelitian ini bertujuan ingin mengetahui faktor-faktor apa saja yang memengaruhi EMP sehingga dapat dijadikan masukan bagi otoritas moneter dalam mengendalikan tekanan terhadap pasar valas. Penelitian ini menggunakan analisis regresi data panel periode 2010.Q1-2018.Q4. Penelitian menunjukkan kredit domestik signifikan negatif memengaruhi EMP. Hal ini tidak sesuai teori yang mengindikasikan bahwa pertumbuhan kredit domestik sejalan dengan peningkatan net capital flows. Transaksi neraca berjalan dan inflasi AS berpengaruh signifikan negatif sedangkan PDB riil tidak berpengaruh signifikan terhadap EMP.Kata kunci: Exchange Market Pressure, EMP, Nilai Tukar, Kebijakan Moneter